Electricity-heat response of energetic materials. Issue 171 (3rd May 2016) - Hua, Xie Xing; Kang, Xu; Sheng, Zhou Hui
ABSTRACT: Transient pulse testing (TPT) is a kind of non-destructive testing technique that can be used to obtain the electro-thermal response of initiators by applying a considerable low current to them. During the testing progress, it is important to ensure that the mining detonators do not function. Thus, it is desirable to know the current-induced temperature increment of the bridgewire. In order to obtain the temperature increment of the bridgewire in the TPT, the simulation of this test is described in this paper. Based on the heat transfer theory, a three-dimensional model is built on the assumption that there is no chemical reaction. Considering the initial conditions and the boundary conditions, the influence of different heat loss factors, heat capacities of bridgewire and currents to the result is studied through the usage of software FlexPDE. Theoretical results are represented in figures. Those results show that this new model is better than model Rosenthal when considering the temperature distribution along the bridgewire.